Failure Analysis of Unconfined Brick Masonry with Experimental Verification - Shukla A.K.; Kumar S.; Maiti P.R. (My University, 2025)
The survival of low rise unconfined masonry structure against earthquakes is very rare even due to low or moderate intensity events. To understand the failure mechanism and cracking pattern of unconfined masonry, a scaled specimen of four unconfined brick was analyzed using finite element software in conjunction with experimental verification. This study started by developing 3D finite element model of unconfined masonry subjected to in-plane loading. Bricks and joints were modeled discretely in the model, allowing for nonlinear deformation characteristics of the both materials. This model exhibits the local effect and is capable of displaying the behavior of masonry walls in which high local stresses and stress gradients are presented in the color contour diagram. The overall result of stress is presented using the von Mises (distortion energy method). The analysis of the model concluded that the unconfined brick masonry specimen structure generally fails along the brick joints, although in-plane shear stresses can cause cracks through the brick in the translation to tensile stress zone. © 2021, ASM International.